x²-3x+2=(x-1)(x-2) Корни по теореме Виета находим
x²-7x+12=(x-4)(x-3)
(x-1)(x-2)(x-3)(x-4)=4
Теперь перемножим 1 и 4 скобки, а также 2 и 3 скобки.
(х-1)(х-4)=х²-5х+4
(х-2)(х-3)=х²-5х+6
Обозначим у=х²-5х
(х²-5х+4)(х²-5х+6)=4
(у+4)(у+6)=4
у²+10у+24=4
у²+10у+20=0 , D=100-4*20=20 , √D=√20=2√5
y₁=(-10-2√5) / 2=-5-√5 , y₂=-5+√5
1)x²-5x=-5-√5 , x²-5x+5+√5=0 , D=25-4(5+√5)=5-4√5 , √D=√(5-4√5)
x₁= [5-√(5-4√5) ]/2 , x₂= [ 5+√(5-4√5) ] /2
2) x²-5x=-5+√5 , x²-5x+5-√5=0 , D=25-4(5-√5)=5+4√5
x₃=[ 5-√(5+4√5) ]/2 , x₄=[ 5+√(5+4√5) ]/2
Ответ: ![x_1=\frac {5-sqrt{5-4\sqrt{5}}}{2} ,\\ x_2=\frac {5+\sqrt{5-4\sqrt{5}}}{2} \\x_3=\frac {5-\sqrt{5+4\sqrt{5}}}{2} \\ x_4=\frac {5+\sqrt{5+4\sqrt{5}}}{2} x_1=\frac {5-sqrt{5-4\sqrt{5}}}{2} ,\\ x_2=\frac {5+\sqrt{5-4\sqrt{5}}}{2} \\x_3=\frac {5-\sqrt{5+4\sqrt{5}}}{2} \\ x_4=\frac {5+\sqrt{5+4\sqrt{5}}}{2}](https://tex.z-dn.net/?f=x_1%3D%5Cfrac+%7B5-sqrt%7B5-4%5Csqrt%7B5%7D%7D%7D%7B2%7D+%2C%5C%5C+x_2%3D%5Cfrac+%7B5%2B%5Csqrt%7B5-4%5Csqrt%7B5%7D%7D%7D%7B2%7D+%5C%5Cx_3%3D%5Cfrac+%7B5-%5Csqrt%7B5%2B4%5Csqrt%7B5%7D%7D%7D%7B2%7D+%5C%5C+x_4%3D%5Cfrac+%7B5%2B%5Csqrt%7B5%2B4%5Csqrt%7B5%7D%7D%7D%7B2%7D+)